2016
DOI: 10.1371/journal.pone.0155901
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of Novel Biomarkers for Prostate Cancer Progression by the Combination of Bioinformatics, Clinical and Functional Studies

Abstract: The identification and validation of biomarkers for clinical applications remains an important issue for improving diagnostics and therapy in many diseases, including prostate cancer. Gene expression profiles are routinely applied to identify diagnostic and predictive biomarkers or novel targets for cancer. However, only few predictive markers identified in silico have also been validated for clinical, functional or mechanistic relevance in disease progression. In this study, we have used a broad, bioinformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 54 publications
(67 reference statements)
6
35
0
1
Order By: Relevance
“…Our analysis identified four significant SNPs mapped to four genes encoding a member of Rho GTPases ( RHOU ), two members of GAPs ( ARHGAP22 and ARHGAP44 ), and a member of GEFs ( ARHGEF10 ). RHOU is upregulated by the Wnt1 signaling in Wnt1‐transformed mouse mammary cells to promote filopodium formation and stress fiber dissolution, and has been reported to regulate tumor cell invasion in prostate cancer by functioning similarly as the Cdc42 small GTPase . While ARHGAP22 and ARHGAP44 trigger local Rac‐GTP hydrolysis, thus reducing actin polymerization required for filopodia formation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis identified four significant SNPs mapped to four genes encoding a member of Rho GTPases ( RHOU ), two members of GAPs ( ARHGAP22 and ARHGAP44 ), and a member of GEFs ( ARHGEF10 ). RHOU is upregulated by the Wnt1 signaling in Wnt1‐transformed mouse mammary cells to promote filopodium formation and stress fiber dissolution, and has been reported to regulate tumor cell invasion in prostate cancer by functioning similarly as the Cdc42 small GTPase . While ARHGAP22 and ARHGAP44 trigger local Rac‐GTP hydrolysis, thus reducing actin polymerization required for filopodia formation .…”
Section: Discussionmentioning
confidence: 99%
“…RHOU is upregulated by the Wnt1 signaling in Wnt1-transformed mouse mammary cells to promote filopodium formation and stress fiber dissolution, 28 and has been reported to regulate tumor cell invasion in prostate cancer by functioning similarly as the Cdc42 small GTPase. 29 While ARHGAP22 and ARHGAP44 trigger local Rac-GTP hydrolysis, thus reducing actin polymerization required for filopodia formation. 14,30 For example, in melanoma cell movement, ARHGAP22 can be activated to suppress mesenchymal movement by inactivating Rac.…”
Section: Discussionmentioning
confidence: 99%
“…Further functional studies revealed that silencing PLA2G7 expression produced antiproliferative, proapoptotic, and antimigratory effects on prostate cancer cells and that statin treatment combined with PLA2G7 silencing synergistically exerted an antiproliferative effect . Recently, Alinezhad et al also identified PLA2G7 as a valid biomarker for prostate cancer and subsequently evaluated its functions in disease‐relevant processes. Similarly, diminished tumor cell invasion and proliferation were detected after silencing PLA2G7 .…”
Section: Biological Functions and Disease Implicationsmentioning
confidence: 99%
“…This list was later updated with examples of good reporting (Altman et al , 2012). A further validation would involve testing using functional biological assays of the presented hypothesis of the identified biomarker (Alinezhad et al , 2016). For genetic risks, a checklist of 25 items recommended for strengthening the reporting of Genetic RIsk Prediction Studies (GRIPS) was further developed particularly to improve the knowledge synthesis and application of information from multiple genetic studies that might differ in design, conduct or analysis (Janssens et al , 2011).…”
Section: Challenges Issues Controversiesmentioning
confidence: 99%